2011
DOI: 10.1002/ejsp.830
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in prejudice and associative versus rule-based forms of transitive reasoning

Abstract: Two experiments examined whether individual differences in prejudice are associated with different reasoning styles when targets and nontargets of prejudice are processed in the same context. High-prejudice and low-prejudice participants studied pairwise relations between four persons (one a prejudice target, three nontargets). Stereotypes were made salient by using specific ethnic names and stereotypic traits to define relations between the targets. Relations between the persons were always stereotype congrue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…On the issue of rapid training, the administration of a five-term extensive-training task in less than 30 minutes is possibly the most rapidly such a task has yet been given to children (e.g., contrast Berens & Hayes, 2007 ; Holcomb et al, 1997 ; Kumaran & Ludwig, 2013 ; Riley & Trabasso, 1974 ; Van der Lely, 1997 ). But over and above rapidity, adopting a modified five-term task could leave researchers with sufficient time available to permit testing of young children in other domains of reasoning or social/interpersonal functioning (e.g., attentional performance, working memory, mathematical competencies, language competencies, understanding other people’s minds, attitudes regarding out groups; Birenbaum & Gutierrez, 2007 ; Coleman et al, 2010 ; Ragni & Knauff, 2013 ; Sedek, Piber-Dabrowska, Maio, & Von Hecker, 2011 ; Von Bastian & Oberauer, 2014 ). This was the original promise of transitive research (Binet & Simon, 1916 ), and it might now be realized.…”
Section: Discussionmentioning
confidence: 99%
“…On the issue of rapid training, the administration of a five-term extensive-training task in less than 30 minutes is possibly the most rapidly such a task has yet been given to children (e.g., contrast Berens & Hayes, 2007 ; Holcomb et al, 1997 ; Kumaran & Ludwig, 2013 ; Riley & Trabasso, 1974 ; Van der Lely, 1997 ). But over and above rapidity, adopting a modified five-term task could leave researchers with sufficient time available to permit testing of young children in other domains of reasoning or social/interpersonal functioning (e.g., attentional performance, working memory, mathematical competencies, language competencies, understanding other people’s minds, attitudes regarding out groups; Birenbaum & Gutierrez, 2007 ; Coleman et al, 2010 ; Ragni & Knauff, 2013 ; Sedek, Piber-Dabrowska, Maio, & Von Hecker, 2011 ; Von Bastian & Oberauer, 2014 ). This was the original promise of transitive research (Binet & Simon, 1916 ), and it might now be realized.…”
Section: Discussionmentioning
confidence: 99%
“…Janis and Frick, 1943) as well as the depth of analytical reasoning (Peeters and Czapinski, 1990). More recently, it has been suggested that individuals scoring comparatively high on social prejudice show impaired reasoning, whereas less prejudiced individuals are more likely to engage in analytical or rule-based reasoning (Sedek et al , 2011).…”
Section: Modern Prejudice and Conjunction Errormentioning
confidence: 99%
“…Respondents scoring higher on modern sexism or modern racism showed greater strength of conjunction error than respondents scoring comparatively low on modern prejudice. This perhaps indicates that for prejudiced individuals, black women form a salient social category (Fiske and Neuberg, 1990; stereotype strength/representativeness: Whaley and Link, 1998), resulting in associative or intuitive rather than rule-based reasoning (Sedek et al , 2011). However, when modern sexism and modern racism were considered jointly in a regression analysis, none of the two variables qualified as a significant predictor of strength of conjunction error – although the direction of potential influence was as expected.…”
Section: Study 1: Modern Sexism Modern Racism and Strength Of Conjunction Errormentioning
confidence: 99%
See 1 more Smart Citation
“…In more abstract terms, we can say “if A > B , and B > C , it then follows that A > C ”. This kind of deductive reasoning is basic to the development and normal functioning of many socio-cognitive processes—from mathematical and text-processing skills, through friendships and the trusting of other people, to generalisations of racial prejudice (Coleman et al, 2010 ; Favrel & Barrouillet, 2000 ; Kim & Song, 2011 ; Markovits, Dumas, & Malfait, 1995 ; Ragni & Knauff, 2013 ; Sedek, Piber-Dabrowska, Maio, & Von Hecker, 2011 ). For example, one might generally trust Mary more than Sally, but might trust Sally more than Trudy.…”
mentioning
confidence: 99%